SP0012 Advanced aps criteria 2016/2017. (15th June 2017) - Meroni, PL
Abstract : The classification of the anti-phospholipid syndrome (APS) is based on the occurrence of arterial/venous thrombotic events and/or pregnancy complications with no identifiable causes in the persistent presence of medium/high titres of anti-phospholipid antibodies (aPL) detectable by solid phase (anti-cardiolipin – aCL or anti-beta2 glycoprotein I – ab2GPI) tests and/or PL-dependent functional coagulation assays (lupus anticoagulant – LA). These classification criteria are currently also used as diagnostic tools. aPL represent a risk factor, consequently the presence of two/three positive diagnostic laboratory tests is a valuable parameter to stratify the patients at highest risk for developing the syndrome/recurrences. The syndrome displays a protean clinical picture depending on the involved tissue/organ. The majority of the clinical (criteria) manifestations are clearly related to vascular ischemic events. However some manifestations apparently cannot be supported by a thrombotic mechanism and alternative pathogenic pathways have been suggested. This is the case for thrombocytopenia, central nervous system involvement such as movement disorders and cognitive abnormalities, and APS nephropathy. Heart valve disease, skin ulcers and livedo reticularis are also frequent events in APS patients and their relationship with vascular thrombosis is unclear. Still debated is the suggestion to include these manifestations as additional clinical diagnostic criteria. The possibility to use all these criteria for ranking the patients as having a definite (standard clinical criteria) or probable APS (non classification criteria) is also debated. The revised criteria for obstetric morbidity comprise otherwise unexplained pregnancy loss. Some of the obstetric criteria might display low sensitivity/specificity for APS. In particular the attribution to aPL of a pregnancy wastage early on gestational course requires the exclusion of a myriad of ethiologies. Conversely, the rate of late foetal losses is very low, making this criterion rather specific. Placenta-mediated obstetric complications provide another critical field: pre-eclampsia and intra-uterine growth restriction are relatively common. To enhance the specificity for APS, the classification criterion included only cases requiring delivery before 34 weeks of gestation. Medium/high aPL titres and double/triple laboratory tests positivities confer a higher risk for pregnancy complications but recent data seem to suggest that also persistent low aPL titres can be predictive for a negative pregnancy outcome. This finding has been recently explained by the availability of large amounts of b2GPI in tissues of the reproductive system. Even though classification criteria have allowed uniformity in APS diagnosis, there still remain some controversies. The field of the laboratory classification criteria is even more in progress. Epitope profiling for anti-b2GPI antibodies is quite promising since the characterization of reactivity against the domain 1 of the molecule appears to display a higher specificity for APS and stronger predictive value than the antibodies against the whole molecule. However, anti-domain 1 assay is less sensitive and cannot replace the standard test at the moment. Antibodies against prothrombin (PT) have been reported to be associated with both the vascular and the obstetric APS, in particular when the antibodies are detectable against a solid phase complex of PT with phosphatidylserine (PS) (the so called anti-PS/PT assay). However a clear evidence for their usefulness in the clinical diagnosis and risk stratification for APS patients as well as their true pathogenic role is still debated. Disclosure of Interest: None declared